2004
DOI: 10.1080/09593332508618386
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a UASB-Digester System Treating Domestic Wastewater

Abstract: The anaerobic treatment of raw domestic wastewater by a novel technology consisting of an Up-flow Anaerobic Sludge Bed (UASB) reactor combined with a completely mixed digester for the stabilisation of the UASB sludge was assessed. A pilot-scale plant of the so-called UASB-Digester system was located at the municipal wastewater treatment facility of Santiago de Compostela (Northwest of Spain). The main aim of the Digester was to enhance the biodegradation of influent solids retained in the UASB reactor at low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Pilot-scale application of the combination of an upflow anaerobic sludge bed (UASB) reactor and a sludge digester, referred to as UASB-digester system, was successful for anaerobic sewage treatment at low temperatures [6][7][8]. In the UASB reactor (at 10-20 • C) dissolved COD is converted; solids are entrapped in the flocculent sludge bed and transported to the digester.…”
Section: Introductionmentioning
confidence: 99%
“…Pilot-scale application of the combination of an upflow anaerobic sludge bed (UASB) reactor and a sludge digester, referred to as UASB-digester system, was successful for anaerobic sewage treatment at low temperatures [6][7][8]. In the UASB reactor (at 10-20 • C) dissolved COD is converted; solids are entrapped in the flocculent sludge bed and transported to the digester.…”
Section: Introductionmentioning
confidence: 99%
“…These treatment conditions were significantly more advantageous for anaerobic digestion. Alvarez et al (2004) treated domestic wastewater (tCOD: 330 -360 mg/L) in an UASB reactor reaching total COD removal efficiencies of 60%. Lew et al (2004) reported COD removal efficiencies up to 75% in a two-phase system (UASB + anaerobic filter) operated at high OLR (around 5 kg COD/m 3 x d); however, solids accumulation in both reactors occurred.…”
Section: Asbr Operationmentioning
confidence: 99%
“…The application of long SRT needs long HRT and therefore large reactor volume, which is economically not feasible. The combination of a UASB and a digester (U-D) has been shown to be successful to treat domestic sewage with high concentrations of suspended organic solids at low temperature (Mahmoud et al 2008, Mahmoud et al 2004, Álvarez et al 2004.…”
Section: Introductionmentioning
confidence: 99%